Pengembangan Media Berbasis Site dalam Pembelajaran Pendidikan Pancasila Kelas 4 di SDN Plampang - Bayu Bumantara; Sutrisna Wibawa; Marzuki (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The importance of improving the quality of Pancasila education learning in grade 4 at SDN Plampang has triggered the development of site-based media as an innovative solution. This research aims to evaluate the effectiveness of this media in increasing students' understanding of Pancasila values. The research method used is Research and Development (R&D). The research results show that site-based media has succeeded in increasing student involvement and making a positive contribution to understanding Pancasila concepts. Pancasila Education Teachers also recognize the key role of this media in presenting material dynamically and accommodating diverse learning styles. Although effective, research identifies barriers, including limited access to technology and teachers' technology skills. Therefore, training and technical support are needed so that site-based media can be used optimally. These findings provide a basis for further development of this media or adjustment of learning methods according to classroom dynamics and technological developments.